Physical assessment for nurses and healthcare professionals - Cox, Carol Lynn; Blackwood, Roger (Hoboken, New Jersey, USA : Wiley-Blackwell, 2019)
"Physical Assessment for Nurses and Healthcare Professionals" offers a practical and comprehensive guide to best clinical practice when taking patient history and physical examination. This accessible text is structured in accordance with the competencies for advanced practice in assessment, diagnosis and treatment as published by the RCN. Following a systematic, systems-based approach to patient assessment, it includes a summary of the key clinical skills needed to develop and improve clinical examination in order to confidently assess, diagnose, plan and provide outstanding care. This important guide includes a highly visual color presentation with photographs and illustrations; features a wide range of key learning points to help guide practice; and offers illustrative examples, applications to practice and case studies. -- From publisher's description.
Adapted from Lecture notes on clinical skills / Robert Turner, Roger Blackwood. 3rd ed.
Interviewing and history taking -- General health assessment -- Examination of the skin, hair and nails -- Examination of the cardiovascular system -- Examination of the respiratory system -- Examination of the abdomen -- Examination of the male genitalia -- Examination of the female breast -- Examination of the female genitalia -- Examination of the nervous system -- Examination of the eye -- Mental health assessment -- Examination of the musculoskeletal system -- Assessment of the child -- Assessment of disability including care of the older adult -- Imaging techniques, clinical investigations and interpretation -- Basic examination, notes and diagnostic principles -- Presenting cases and communication.
Preceded by Physical assessment for nurses / edited by Carol Lynn Cox. 2nd ed. 2010.
Based on Lecture notes on clinical skills / Roger Blackwood, Chris Hatton. 4th ed. 2003.
Includes bibliographical references and index.
CHS
Text in English
Keywords: Nursing Assessment